Management of primary aldosteronism in patients with adrenal hemorrhage following adrenal vein sampling: A brief review with illustrative cases. Issue 12 (9th September 2017) - Hannah‐Shmouni, Fady; Demidowich, Andrew; Alves, Beatriz Rizkallah; Paluch, Gabriela Dockhorn; Margarita, Dionysiou; Lysikatos, Charalampos; Belyavskaya, Elena; Chang, Richard; Stratakis, Constantine A.
Abstract : The authors describe the clinical investigation of two cases of primary aldosteronism with adrenal hemorrhage (AH) following adrenal vein sampling. A literature review was conducted regarding the medical management of primary aldosteronism in patients with AH following adrenal vein sampling. Guidelines on the management of primary aldosteronism with AH following adrenal vein sampling are lacking. The two patients were followed with serial imaging to document resolution of AH and treated medically with excellent blood pressure response. Resolution of AH was achieved, but a repeat adrenal vein sampling was deferred given the increased morbidity risk associated with a repeat procedure.